Pendampingan Pemberdayaan Ibu Rumah Tangga dalam Program Teras Hejo di Desa Cileles Kecamatan Jatinangor, Jawa Barat - Sumarno, Dwi Agus; Rozie, Azharisman; Nurhadi, Nurhadi; Wijaya, Riko (Civitas Consecratio: Journal of Community Service and Empowerment, 2024)
The aim of this community service is to empower housewives in Sumedang Regency by utilizing home yard spaces for the cultivation of vegetables and fruits to improve food security and enhance family income. The main issues faced include limited access to healthy food and low family income, which affects the quality of life. In addition, the untapped potential of home yards hinders efforts to meet food needs and improve the family economy. The methods used in this program include training in vegetable and fruit cultivation techniques, mentoring in yard management, and providing knowledge on household financial management. The results of the program show an improvement in the ability of housewives to manage their yards to produce economically valuable food commodities, thereby enhancing food security and family income. The Teras Hejo program successfully improved housewives' access to healthy and nutritious food and had a positive impact on family income through the sale of cultivated products. Based on these findings, it is recommended to expand the program by involving more relevant stakeholders, including the government and financial institutions, to support the sustainability and scaling of micro-enterprises based on home yard cultivation.